Sharia Bank Product Marketing Strategy Through Social Media - Nurul Aten; Yuliana Dwi Puspita Sari (Yayasan Darussalam Bengkulu, 2022)
The purpose of writing this scientific work is to increase insight into thought patterns, attitudes and experiences as an effort to improve the quality of learning, namely by understanding the nature of a Sharia Bank Product Marketing Strategy that applies marketing components on social media. The research in this scientific work is motivated by the very rapid development of technology, especially internet technology, where its development can change a person's behavior or habits in deciding to buy something, so marketers need to adopt sharia bank marketing product strategies to increase sales on social media that utilize development of internet technology, namely social media. Hearing the word marketing is often associated by many parties with sales, sales promotion, advertising, promotions or products. In fact, people often equate the profession of marketer with sales. However, marketing is actually not as narrow as many people identify, because marketing is different from sales. Marketing is more